Industrial x-ray inspection system with improved image characterization using blind deblurring based on compressed-sensing scheme. Issue 3 (4th May 2017) - Kim, Kyuseok; Park, Soyoung; Kim, Guna; Cho, Hyosung; Je, Uikyu; Park, Chulkyu; Lim, Hyunwoo; Lee, Hunwoo; Lee, Dongyeon; Park, Yeonok; Woo, Taeho
ABSTRACT: An industrial x-ray inspection system has recently established by our group to examine large and dense objects available in industry. It consists of an industrial x-ray generator having a tube voltage of 450 kV and a focal spot size of 1 mm, a flat-panel detector having a pixel size of 200 µm and a pixel dimension of 2048 × 2048, and a mechanical support for object's installation. For improving the image characteristics of the system, an effective blind deblurring method based on compressed-sensing scheme is reported. Blind deblurring is the image restoration by estimating the original image and the degradation mechanism using partial information on both. Compressed-sensing is a relatively new mathematical theory for solving the inverse problems. Systematic measurements were performed and the image characteristics of the restored images were quantitatively evaluated using several image-quality indicators. The results demonstrate that the deblurring method is effective for industrial x-ray inspection systems.